UJI FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN RAMBUTAN (Nephelium lappaceum)DENGAN METODE DPPH (1,1-diphenyl-2-picryhidrazyl) - Pangaribuan, Fransiscus X. Rico; Sitorus, Saibun; Saleh, Chairul (JURNAL ATOMIK, 2016)
Research about antioxidant test of rambutan leaves extract (Nephelium lappeceum) by using radical compound DPPH (1,1-diphenyl-2-picrylhidrazil) has been carried out. This research aims to determine antioxidant activity level of rambutan leaves extract and to detrermine kind of secondary metabolites in it. Concetration taht used in rambutan leaves extract are 5 ppm, 10 ppm, 25 ppm, 50 ppm dan 100 ppm. Result of fitochemical shows that secondary metabolites in n-hexane extract were alkaloid and flavonoid, secondary metabolites in ethyl acetat extract were alkaloid, flavonoid and phenolic, secondary metabolites in ethanol extract were alkaloid and phenolic where as secondary metabolites in ethanol-water extract weas phenolic. IC50 value in each extract of n-hexane, ethyl acetat, ethanol and ethaol-water in a row were 56,48 ppm; 16,82 ppm; 25,47 ppm and 8,59 ppm. The highest antioxidant activity level was in ethanol-water.